Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas V Sekolah Dasar Muatan IPA Menggunakan Model Ingat - Soraya Putri Rosadi; Aslamiah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this research is low activity, critical thinking skills, and student learning outcomes. Efforts to solve the problem use the INGAT model (Problem Based Learning, AIR (Auditory, Intellectually, Repetition), Talking Stick). The purpose of this study is to describe teacher activities, analyze increased activity, critical thinking skills, and student learning outcomes. The approach taken is a qualitative approach with the type of Classroom Action Research which is carried out in 4 meetings. The research subjects were 13 students of class V at SDN Belitung Selatan 9 Banjarmasin. Data collection techniques through observation of teacher activities, student activities and critical thinking skills then for learning outcomes obtained through written tests. The results of the study showed that the teacher's activities were carried out "very well". Student activity increased with the criterion "Almost All Active". Students' critical thinking skills increased with the criteria "Almost All Skilled". For student learning outcomes reach 100% with the "Complete" criteria. Based on the results of this study it can be concluded that learning using the INGAT model can increase student activity, students' critical thinking skills, and student learning outcomes.